A Case Report of Femoral Hematoma following Obturator Nerve Block - Kiyoshi Moriyama; Kumi Moriyama; Tomoki Kohyama; Kunitaro Watanabe; Mieko Chinzei; Tomoko Yorozu (Case Reports in Anesthesiology)
Background. When an obturator nerve block (ONB) is performed, the conventional landmark method or ultrasound-guided method is used. The major complications of this block are hematoma, but there are very few reports of its complications. We encountered massive bleeding and a huge hematoma after ONB. Case Presentation. A 95-year-old female underwent transurethral resection of the bladder tumor. Induction of anesthesia was accomplished via spinal anesthesia and right ONB using the landmark method. Postoperatively, subcutaneous bleeding was detected in the lower right interior thigh. Concentrated red cell transfusion was conducted to address the anemia. There was no subsequent expansion of the hematoma. It resolved on postoperative day (POD) 53. The hematoma was deemed to be inadvertently introduced due to an obturator artery puncture during the obturator nerve block. Conclusions. Close attention is necessary to avoid advancing the needle too deep into the obturator during obturator nerve block.